(untitled) (TSUL LEGAL REPORT, 2026)
This article provides a comprehensive analysis of journalistic investigation, examining its theoretical foundations, developmental stages, and position within contemporary journalism. By synthesizing scholarly sources and practical examples, the study clarifies the essence, social functions, and distinct characteristics of the investigative branch. It further explores the legal framework and ethical principles governing information collection and dissemination, emphasizing the journalist’s rights and obligations. Special attention is directed toward the role of investigative journalism in facilitating public oversight and strengthening the transparency and accountability of civil society institutions. The research scientifically substantiates the genre’s potential for identifying societal problems, monitoring state bodies, combating corruption, and promoting social justice. Additionally, the study distinguishes between “journalistic investigation” and “journalistic inquiry,” comparing national and international scholarly perspectives on their objectives and scope. The article concludes by defining the significance of the investigative genre within modern journalism theory and the global information landscape.